1989
DOI: 10.1152/ajpgi.1989.257.5.g798
|View full text |Cite
|
Sign up to set email alerts
|

Prostanoids in regulation of postprandial jejunal hyperemia and oxygen uptake

Abstract: The role of prostanoids in regulation of jejunal blood flow (JBF) was studied in anesthetized dogs. Intra-arterial infusions of arachidonate produced biphasic changes and dose-dependent decreases in jejunal vascular resistance (JVR) in untreated and aspirin-pretreated dogs, respectively; mefenamate abolished these responses. The jejunum released prostaglandin I2 (PGI2) greater than PGE2 greater than thromboxane A2 (TXA2) (radioimmunoassay) under resting conditions, and food enhanced the release of PGE2 greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Following the observations that L-NAME produces a sustained increase in systemic arterial blood pressure and motility, we determined whether or not the jejunal motility is a consequence of the increase in systemic arterial blood pressure. Previously we have shown that a single intravenous injection of mefenamate (10 mg kg-') produces a sustained increase in blood pressure (Mangino & Chou, 1986;Chou et al, 1989). Therefore, utilizing the same jejunal preparation and the same protocol as in series II, jejunal lumen pressure add blood flow and systemic arterial pressure were recorded before and after a single intravenous injection of mefenamate (10 mg kg-') for 1 h.…”
Section: Methodsmentioning
confidence: 99%
“…Following the observations that L-NAME produces a sustained increase in systemic arterial blood pressure and motility, we determined whether or not the jejunal motility is a consequence of the increase in systemic arterial blood pressure. Previously we have shown that a single intravenous injection of mefenamate (10 mg kg-') produces a sustained increase in blood pressure (Mangino & Chou, 1986;Chou et al, 1989). Therefore, utilizing the same jejunal preparation and the same protocol as in series II, jejunal lumen pressure add blood flow and systemic arterial pressure were recorded before and after a single intravenous injection of mefenamate (10 mg kg-') for 1 h.…”
Section: Methodsmentioning
confidence: 99%
“…The importance of intrinsic and extrinsic nerves in gut has been investigated to some extent and has been ascribed a very limited role in the postprandial hyperemic response (39 -41), although nervous components cannot be completely ruled out (56). Some studies have addressed the importance of endocrine (21) and paracrine factors, such as histamines (22), prostaglandins (17), and adenosine (45,46) but with apparently varying results. The most likely explanation seems to be that metabolic factors such as O 2 , H ϩ , and CO 2, as well as adenosine and lactate mediate the postprandial hyperemia (43,49), and glucose has been found to stimulate adenosinemediated NO production (36).…”
Section: Cardiovascular Parametersmentioning
confidence: 99%
“…The chemical stimulus is dependent on the composition of the feed and it has been noted that different nutrients are not equally essential in inducing the postprandial hyperemia (Chou et al, 1972;Kvietys et al, 1981;Siregar and Chou, 1982). The exact mechanism controlling the hyperemia in mammals is under debate but may involve direct effects from the absorbed nutrients on the vasculature , endocrine factors (Biber, 1973;Chou et al, 1977;Chou et al, 1984;Fara et al, 1972), non-metabolic vasoactive factors (Chou et al, 1989;Chou and Siregar, 1982;Sawmiller and Chou, 1988;Sawmiller and Chou, 1990), metabolic vasoactive factors (Bohlen, 1980a;Bohlen, 1980b;Bohlen, 1998a;Pawlik et al, 1980) and neural mechanisms (Biber, 1973;Kato et al, 1989;Takagi et al, 1988). There are, however, large variations in mammals reported in the literature, which, to some extent, can be explained by large interspecies differences.…”
Section: Introductionmentioning
confidence: 99%